Peran Mediator dalam Penyelesaian Sengketa Ekonomi Syariah di Pengadilan Agama Sleman - Dwi Wiwik Subiarti (Universitas Islam Indonesia, 2017)
This study aims to examine and analyze the role of mediators in resolving sharia economic disputes in Sleman Religious Court. We also aim to determine the obstacles faced by mediators when mediating sharia economic disputes in Sleman Religious Court. This research is a normative legal research using a legislative approach and a case-study approach. Based on the results of the study, we find that the role of mediators in solving sharia economic disputes in Sleman Religious Court is generally unsatisfactory due to several obstacles they face although for some cases of sharia economic disputes the role of mediators has been strong enough to achieve agreement deeds . Though remaining insignificant, the role of mediators has been able to reduce the number of sharia economic cases to be resolved by investigating judges.Keywords: The role of mediators; sharia economic disputes; religious court